Energy storage for complementary services in grid-tied PV systems - Muller-Pollmann, Nicolas (2021)
The continuous increase in penetration of renewable-based power plants together with the intermittent and variable nature of those natural resources have made grid stability issues a major concern, imposing limitations to higher penetration rates. Energy Storage Systems (ESS) have arise as an enabling technology capable of providing PV/ESS configurations with additional capabilities, as such as ancillary or complementary services.